2019
DOI: 10.1186/s13052-019-0673-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of procalcitonin for overall and complicated acute appendicitis in children: a meta-analysis

Abstract: Background Diagnostic value of procalcitonin (PCT) for acute appendicitis (AA) has been evaluated in adult patients, but the application in children remains controversial. The aim of this study was to evaluate the diagnostic value of PCT for overall and complicated AA in children. Methods The PubMed, EMBASE, Web of Science, Cochrane Database of Systematic Reviews, Chinese National Knowledge Infrastructure, and Wanfang were searched along with reference lists of relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…Yu et al reported that PCT had little value in diagnosing AA, with lower diagnostic accuracy than CRP and WBC, but a greater diagnostic value in identifying complicated AA [58]. In a recent meta-analysis, it was confirmed that PCT was more accurate in diagnosing complicated AA, with a pooled sensitivity of 0.89 (95% CI 0.84-0.93), specificity of 0.90 (95% CI 0.86-0.94), and diagnostic odds ratio of 76.73 (95% CI 21.6-272.9) [59].…”
Section: Q14: What Is the Role Of Serum Biomarkers In Evaluating Pementioning
confidence: 89%
“…Yu et al reported that PCT had little value in diagnosing AA, with lower diagnostic accuracy than CRP and WBC, but a greater diagnostic value in identifying complicated AA [58]. In a recent meta-analysis, it was confirmed that PCT was more accurate in diagnosing complicated AA, with a pooled sensitivity of 0.89 (95% CI 0.84-0.93), specificity of 0.90 (95% CI 0.86-0.94), and diagnostic odds ratio of 76.73 (95% CI 21.6-272.9) [59].…”
Section: Q14: What Is the Role Of Serum Biomarkers In Evaluating Pementioning
confidence: 89%
“…Accurate differentiation between simple and complicated appendicitis is emerging as a potentially key issue as the historical standard of care, that is prompt appendectomy, is increasingly questioned in pediatric patients [7,16]. Since AA has a rate of been complicated of approximately 40%, different methods for predicting complicated [7,13,[17][18][19]. This study not only describe the independent risk factors for complicated appendicitis, but establish early identification of risk factors in order to predict complicated appendicitis.…”
Section: Discussionmentioning
confidence: 95%
“…In patients with atypical forms of AA, routine diagnostic laboratory workup for suspected AA should include WBC, the differential with the calculation of the absolute neutrophil count (ANC), neutrophil -to-lymphocyte ratio (NLR), C-reactive protein (CRP), red cell distribution width [48,49] and urinalysis. Recently, ischemia-modi ed albumin (IMA) and procalcitonin levels have been used to determine the prediction of severity in AA patients [28,29]. A combination of clinical examination (with new palpation sign), laboratory tests, and US may signi cantly improve diagnostic sensitivity and speci city and eventually replace the need for CT scan in both women of childbearing age and children [30,37].…”
Section: Discussionmentioning
confidence: 99%